HARRIETT’S STRUGGLE FROM HATRED TOWARD THE WHITE PEOPLE IN LANGSTON HUGHES’ NOT WITHOUT LAUGHTER - Emelinda Oktavia Dhoy (Humaniora Scientia, 2018)
This  article discusses Harriett’s struggles from hatred toward the white people in Langston Hughes’ Not Without Laughter. It aims to (1) explain Harriett’s struggles from hatred toward the white people in Langston Hughes’ Not Without Laughter and (2) explain the effects of Harriett’s struggles toward herself. This article focuses on the novel Not Without Laughter as the main source of data. The researcher uses articles and online sources as the references. This article applies four theories.They are theory of feminism, black women struggles, psychology and hatred. In addition, psychological and sociological approach are also used in this article. Library research is applied for data collection technique. The analysis focuses on the Harriett’s struggles from hatred toward the white people in Langston Hughes Not Without Laughter. Langston Hughes in his novel describes about the struggles of black women to equate their position with the white people and free themselves from the segregation and discrimination in the United States. Harriett faces many problems in order to against her hatred toward the white people. Harriett becomes a person who does not believe in God. She oppose her mother’s word, and being an avenger because she really hates the white people. When her mother passes away, Harriett finally regrets her actions. She  promises not to do the same mistakes as she has already done toward the white people. Harriett becomes a responsible woman to her family, and she finally raises up her race to get the same rank as the white people.